How do I look? - Ramam, M (Indian journal of dermatology, venereology, and leprology, 2014)
The number of advertisers a journal attracts is another measure of its worth though this is more commonly used in assessing or comparing general interest periodicals rather than medical journals. In the rare situation where expertise in a subject is limited to a small number of people and more than one article on the topic has been submitted around the same time, we will seek the referee's permission before sending him the second article.